The role of influencer marketing moderation in consumer journeys and digital trust in online purchasing decisions - Owen De Pinto Simanjuntak; Robert Roy Purba; Eva Margareth Sarah (Jurnal Konseling dan Pendidikan, 2025)
This study aims to analyze the influence of consumer journey, digital trust, and consumer purchasing decisions with influencer marketing as a moderation variable in students who are active users of the Shopee e-commerce platform in Batam City. This study also examines the role of influencer marketing as a moderation variable in the relationship between consumer journey and digital trust on consumer purchase decisions. The method used is quantitative research with a descriptive and verified approach. The research population is students in Batam City and has made transactions on Shopee in the last six months. The sampling technique used purposive sampling with a total of 100 respondents. Data analysis was carried out using multiple linear regression analysis with the help of SmartPLS software version 4.0. The results of the study show that consumer journey, digital trust, and influencer marketing have a positive and significant effect on consumer purchase decisions. Additionally, influencer marketing has been shown to moderate the relationship between consumer journeys and digital trust in consumer purchasing decisions positively. This means that the existence of relevant and popular influencers among students is able to strengthen the influence of shopping experience and digital trust on purchase intentions. These findings underscore the importance of digital marketing strategies that combine a good user experience, digital trust, and collaboration with influencers in improving purchasing decisions among college students. The implications of this study for e-commerce like Shopee are that marketing strategies that optimize the consumer experience, build digital trust, and collaborate with relevant influencers can increase purchase conversions, especially from the student segment.